Dystocia due to muscular hypertrophy of fetal neck in a buffaloes - HONPARKHE, M; DHINDSA, S S; GHUMAN, S P S; Kumar, Ajeet (The Indian Journal of Animal Reproduction, 2007)
A rare case of dystocia in a buffalo due to muscular hypertrophy of fetal neck was relieved by partial foetotomy and described in this report.
Keywords: Buffalo; Dystocia; Muscular hypertrophy